Inversion tectonics and mineral system in the Ucayali Subandean fold and thrust belt - Joselyn Medina; Patrice Baby (Instituto de Ingenieros de Minas del Peru, 2023)
Recent reports indicate potential for metallic mineralization in the Ucayali Subandean fold and thrust belt related to a mineral system with a magmatic source. In this work, we show the control of Andean tectonics in metallic mineralization in Ucayali and discuss the key components of the mineral system.